ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPERCAYAAN NASABAH MUSLIM PENGGUNA MOBILE BANKING DI BANK MUAMALAT INDONESIA 118 KANTOR CABANG PEMBANTU KUDUS - Sa'diyah, Mahmudatus; Aziroh, Nur (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
This research intends to know the factors that influence the level of customer confidence Muslims mobile banking users in Bank Muamalat Indonesia Holy Branch Office. The sample in this study amounted to 160, which is a mobile banking users in Bank Muamalat Indonesia Holy KCP. Statistical tool used is Structural Equation Modeling (SEM). Data were analyzed using statistical software AMOS 16.0. The results of this study indicate that shared value is a factor that affects customer confidence in mobile banking users, while the communication has not been able to increase customer confidence in mobile banking users and opportunistic behaviors control has not been able to increase the confidence of users of mobile banking.